The future of the welfare state: European and global perspectives (Aldershot, 2006)
"This book challenges the common beliefs that the European welfare states are already in or are heading towards crisis and that the process of globalisation necessarily puts paid to any hopes of eventual worldwide welfare. Instead it is argued that a proper understanding of the future role of the welfare state requires a broader social perspective that encompasses the interaction of economic, political and social processes. The aim of this book is to provide an interdisciplinary analysis of the practical and theoretical challenges which the the welfare state (and progress towards world welfare) can and must meet in the future."